Pentecostalism and heteronormative God-talk in modern South Africa: A decolonial approach - Shingange, Themba (Verbum et ecclesia, 2023)
This article reflects on the use of heteronormative God-talk within African Pentecostalism in modern South Africa. God-talk has often been used as a tool to push specific socio-political ideologies within the global community and in discourses about gender and sexuality. In Africa, these discourses are often characterised by debates and influenced by normative, moral religious and Christian views. Research indicates that African Pentecostalism is one of the fastest-growing Christian movements in the world and it has great influence on sexual moral discourses. The advent of neo-Pentecostalism in South Africa was marked with the abuse of God-talk. Different media platforms reported on the commercialisation and abuse of religion as Pentecostal prophets used God-talk often disguised as prophecy to perform unusual practices and to make religious remarks regarding gender identities and sexualities. This forced and reinforced the hegemony of heterosexuality in society. Therefore, the decolonial motif was applied in this article to reflect on the coloniality of power embodied in God-talk. Decoloniality can be a tool that can reveal both the liberating and oppressive elements in the use of God-talk in South Africa. Intradisciplinary and interdisciplinary implications The decolonial move here was motivated by the progressive post-heteronormative South African paradigm. The article used the interdisciplinary approach, namely socio-political sciences and Missiology to challenge the abuse of God-talk within contemporary Pentecostalism in South Africa. Positive use of God-talk can liberate both the church and society by transforming the traditional heteronormative views and by empowering congregants irrespective of their gender or sexuality. Such transformation can be possible if post-heteronormativity can be embraced by both church and society.